Toxicity of several contact insecticides to Tribolium castaneum (Herbst) populations after selection with pirimiphos-methyl and deltamethrin - Andrić, Goran G; Pražić Golić, Marijana; Kljajić, Petar (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2016)
Laboratory bioassays were conducted to detect possible alteration in susceptibility of two field Tribolium castaneum (Herbst) populations (sampled in a warehouse in Nikinci and a silo in Jakovo) to dichlorvos, malathion, chlorpyrifos-methyl, pirimiphos-methyl, deltamethrin and bifenthrin after previous selection with the LD80 of pirimiphos-methyl and deltamethrin.Data from the topical application bioassays show that chlorpyrifos-methyl was the mosttoxic insecticide to T. castaneum adults of the Nikinci population selected with pirimiphosmethyl and deltamethrin, while malathion was the weakest, and both selection procedures changed/reduced significantly only the toxicity of deltamethrin and bifenthrin, increasing their resistance ratios (RR) at the LD50 from 1.1 to 1.8 (bifenthrin) and from 0.9 to 2.2 (deltamethrin). Deltamethrin was the most toxic insecticide for Jakovo adults selected with the LD80 of pirimiphosmethyl, while malathion was again the least toxic. Selection of that population had no effect on insecticide toxicity, except of malathion, which had a rise in RR at the LD50 from 26.0 to 29.8.
Keywords: Insecticides; Toxicity; Red flour beetle